Dakwah MMI (Mengurai Kekerasan Sosial pada Diskusi di LKiS Yogyakarta) - Abdul Jalil (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2016)
Attacks promoted by certain elements during a discussion in LKiS of course disturb the society, moreover when they causes social violence. At the same time, the dynamic and diverse condition of society often interprets a problem according to the social condition so the problem never comes to an end. In accordance to the fact, the research was conducted to investigate why the social violence happens easily and it is always identical with Majlis Mujahidin Indonesia (MMI). The research applies descriptive analysis method using the primary and secondary data by learning the locus of research on the social violence happened after the discussion in LKiS Yogyakarta. The internal factors as causes that need to get serious attention from all components of the nation include the poor condition of social welfare, the lack of religious knowledge and the need of a figure who is able to enlighten the society. These factors cause the society behave cruelly. Meanwhile, there are other groups of people who feel that their faith was disturbed, and the absent function of existing security system, have resulted the social violence as an answer for the people who commit acts of violence.Keywords: Models of Propagation, MMI, Social Violence, and LKiS.